Manfaat Asesmen dalam Pembelajaran Anak Berkebutuhan Khusus - Hartini, Jusri; Matasari, Ocvy; Andriani, Opi; wicaksono, nurzahra Fathiyanabila (Jurnal Pendidikan Vokasi dan Seni, 2023)
Children with disabilities have different learning needs from children in general and tend to experience learning difficulties. Therefore, teachers need to carry out appropriate assessments in order to meet the learning needs of each student, including students with disabilities. The method used in this research is a literature review study or literature review. Literature study is a research design used to collect data sources related to a topic found in the field. Data collection for the literature study was carried out using the Google Scholar search tool. The filtering results that were appropriate and needed were 5 National Journal articles based on the articles found and analyzed. The results of this research are the benefits of assessment in the education of children with special needs, namely to obtain information about students, which later the information collected can be used as treatment or action taken by schools and teachers in providing services and improvements to students in the process. learn according to the conditions of each individual.